Who suffers during recessions in Brazil? - Túlio Cravo; Caroline Schimanski (Inter-American Development Bank (IDB), 2019)
While the relationship between business cycles and employment is a topic of continuing interest, it has received limited attention in the literature focusing on developing countries. This study adds to the literature as it analyzes the heterogeneous correlations of the business cycle with different age, education, and ethnic groups by gender in a developing country setting, controlling for other characteristics. Using data from Brazil's monthly PME employment surveys between 2002 and 2016, regressions are estimated to assess how business cycles affect employment in specific demographic groups. The results provide evidence of large heterogeneities among demographic groups. Interestingly, unemployment rates in levels across demographic groups are not necessarily aligned with the sensitivity of these demographic groups' (un)employment and participation rates to economic crises.
Keywords: E24; J21; J23; J24; J46; 330; Labor Market; Brazil; Developing Countries; Business Cycles; Heterogeneous Effects; Employment Dynamics